Standardization of an in-house multiplex real-time polymerase chain reaction for the simultaneous detection of Toxoplasma gondii, Rubella virus, cytomegalovirus, herpes simplex Virus 1 and 2, and Treponema pallidum infection among pregnant women - Prashanth Rajendiran; Nithiyanandan Saravanan; Mageshbabu Ramamurthy; Sathish Sankar; Rajasekar Aruliah; Balaji Nandagopal; Gopalan Sridharan (Wolters Kluwer Medknow Publications, 2021)
Background: An in-house multiplex real-time polymerase chain reaction (PCR) was developed in two cocktails for the identification of six Toxoplasma gondii, Rubella virus, cytomegalovirus, herpes simplex virus (1 and 2), and Treponema pallidum (syphilis) (TORCH-S) agents, which causes congenital infection among pregnant women. Objective: Standardization and validation of an in-house multiplex real-time PCR assay for the detection of TORCH-S infection. Methods: This study was conducted from February 2017 to February 2019. Primers specific for T. gondii, Rubella virus, cytomegalovirus, herpes simplex virus (1 and 2), and T. pallidum were designed using Primer3 software (https://bioinfo.ut.ee/primer3-0.4.0/). The primer sequences obtained were subjected to BLAST analysis using BLAST database. Synthetic DNA was obtained to use as positive control templates for all the six TORCH-S agents. The lower limit of the detection was performed using plasmid construct for each virus serially diluted from 10−1 to 10−9. Results: An in-house multiplex real-time PCR was standardized and validated in two cocktails for TORCH-S agents, cocktail-1 (HSV1, rubella, and T. gondii), and cocktail-2 (HSV2, CMV, and T. pallidum). The lower limit of the detection for HSV1, rubella, and Toxoplasma were 60.7 copies/10 μl input, 76.4 copies/10 μl input, and 34.4 copies/10 μl input and for HSV2, CMV, and T. pallidum were 80.8 copies/10 μl input, 166 copies/10 μl input, and 43.7 copies/10 μl input, respectively. Conclusion: TORCH-S infection is one of the significant reasons for irregular pregnant outcomes. It is absolutely important to screen TORCH-S infection for women who had the histories of abnormal pregnancies to prevent birth defects and perinatal complications. This multiplex real-time PCR assay provides a rapid, sensitive, and specific technique to detect these six TORCH-S agents.